#### Answer

=

#### Work Step by Step

|-2| = 2
-1 - (-3) = 2
Both sides of the statement are equal, so |-2| = -1 - (-3).

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

=

|-2| = 2
-1 - (-3) = 2
Both sides of the statement are equal, so |-2| = -1 - (-3).

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.